Respuesta :

Answer:

B

Step-by-step explanation:

2x - 3 - x = 2 + 2x - 5

add like terms

x - 3 = -3 + 2x

subtract 2x to x on the other side

x - 3 = -3 + 2x

-2x            - 2x

-x - 3 = -3

add 3 to the other side

-x - 3 = -3

  + 3   + 3

-x = 0

x = 0

Answer:

B) 2x-3-x=2+2x-5 has exactly one solution.

Step-by-step explanation:

A) -2x-1+5x=4+3x-1

-2x+5x-1=3x+3

3x-1=3x+3

3x-3x-1=3

0-1=3

-1=3

no solution

-----------------------

B) 2x-3-x=2+2x-5

x-3=2x-3

x-2x-3=-3

-x-3=-3

-x=-3+3

-x=0

x=0

Has exactly one solution.

-----------------------------------

C) 6x+2-4x=4+2x-8

2x+2=2x-4

2x-2x+2=-4

2=-4

no solution.

----------------------------

D) 5x+4x=3(3x-8)

9x=3(3x-8)

3x=3x-8

3x-3x=8

0=8

no solution.